Analysis of volatile compounds in flesh, peel and seed parts of pumpkin (Cucurbita maxima) cultivated in Ethiopia using gas chromatography-mass spectrometry (GC-MS) - Mulu Hagos; Estifanos Ele Yaya; Bhagwan Singh Chandravanshi; Mesfin Redi-Abshiro (International Journal of Food Properties, 2022)
This study was aimed to analyze and compare the volatile compounds of flesh, peel and seed parts of the pumpkin (Cucurbita maxima). The volatile compounds were extracted from three different parts of pumpkin using a hydro-distillation method. Extracts from the three different parts of pumpkin were injected into the gas chromatography-mass spectrometry system. Mass spectral data were collected from 40–650 m/z. The volatile components were identified by matching their mass spectra with those of reference compounds recorded in the mass spectral library and retention indices. A homologous series of n-alkanes (C9–C30) were run under the same operating conditions as the volatile oils to determine the retention indices. The chromatographic analysis revealed the presence of 15, 23 and 28 components in the essential oils obtained from flesh, peel and seed parts of pumpkin representing a total composition of 81.5, 84.4, and 97.7%, respectively. Out of volatile compounds that were identified, three were common to all 3 parts, six were common to flesh and peel, eight were common to peel and seed, and five were common to flesh and seed. Hydrocarbons (43.6%) and esters (26.4%) were the most abundant volatile compounds identified in the seed part of pumpkin followed by sulfur containing compounds (30.3%) in the peel, (23.7%) in the flesh and (12.7%) in seed parts of pumpkin. Terpinene compounds were also found (23.5%) in the flesh, (22.9%) in the peel and (5.02%) in the seed parts of pumpkin. The compositions of the volatile compounds vary from one part to another of the pumpkin. Some of the volatile chemicals discovered in this investigation matched with the published data from other nations. According to the findings of this study, different volatile chemicals detected in various parts of the pumpkin indicated increased medicinal and nutritional potential.